Loneliness in emerging adulthood: A qualitative study using cultural probes and in-depth interviews - Berit Kjærside Nielsen; Lise Arnth Nielsen; Mathias Lasgaard (Current Research in Behavioral Sciences)
Background: Loneliness has become a great public health concern in the Western world, with emerging adults being particularly vulnerable. Prolonged loneliness in emerging adults is associated with poor mental health such as symptoms of depression and anxiety that may have negative implications for health and well-being in later life. Aim: To explore and gain a deeper understanding of how loneliness develops over time and how it is experienced by emerging adults in their everyday life. Methods: The study is a thematic analysis of qualitative data consisting of cultural probes and in-depth interviews. Participants were recruited through targeted advertising on social media. During a week, participants aged 18 to 25 years old completed a cultural probe comprising open and evocative activities. These activities provided an opportunity for participants to explore their day-to-day existence, thereby contributing to the portrayal of their individual stories concerning loneliness in everyday life. After reviews of the cultural probes, in-depth interviews were conducted. Results: Participants were 21 emerging adults (mean age 21.3), three men and 18 women. Following thematic analysis of the cultural probe material and interview data, three overarching themes were conceptualized: 1) The many faces of loneliness, 2) The interplay between low self-esteem, intrusive thoughts, and mental health in shaping loneliness, and 3) The duality of coping strategies. Conclusion: The findings from this qualitative study offer in-depth insights into the experience of loneliness among emerging adults, highlighting its multifaceted nature and interplay with mental health. Participants' narratives revealed a duality of coping strategies, where engaging in distracting activities provided temporary relief but perpetuated long-term loneliness, and attempts to reconnect with others were sometimes hindered by past experiences. The findings contribute to a richer understanding of loneliness during this pivotal life phase, with implications for interventions needed to address social disconnectedness, thereby contributing to the broader conversation on mental health and well-being.